S’approprier, c’est résister. Appropriations spatiales et mobilisation infra-politique des femmes en immobilité résidentielle et sociale dans les bidonvilles de Salé (Maroc) - Myriame Ali-Oualla (L’Année du Maghreb)
Morocco’s shantytowns appeared in the first decades of the last century, bringing together people who had come from the countryside and the hinterland to meet the growing demand for labour in the imperial cities, which at that time represented the chief means of economic development. A relatively loose regime of urban regulation allowed sporadic settlement by small groups from the same districts, often from the same villages, creating communities that shared cultural references, ways of living, migratory routes and spatialised collective memory – attributes necessary for anchoring a new identity.Thanks to the evolving ambitions of the new arrivals, the shantytown has become a stepping stone to urban living, and one of the most viable housing alternatives, permitting easy and cheap access to urban amenities. However, what is perceived as a springboard for eventual socio-economic ascent and legitimate settlement in the city is transformed into a place of inertia, feeding totalising and disqualifying identity assignments. Households are kept waiting by a lack of responsiveness on the part of the authorities, and by their inability to provide suitable housing alternatives. Socio-economic immobility is coupled to residential immobility, reinforcing the stigma attached to the place of residence. For the women of the shantytown, who live in a context that greatly conditions the assignment of domestic roles, this stigma is exacerbated by gendered immobility. As a “minority within a minority”, they experience an inertia that translates into captive territorialities, and an intense and active domestic appropriation that makes the domain of intimacy a resolutely feminine world.This status quo is challenged by the residents of the shantytown, who use collective spatial appropriation and the strategy of “non-movement” as a means of resisting being rehoused in outlying areas, in flats that are often unsuitable for the needs and sizes of their households. Sub-political mobilisation through the material consolidation of living space, and the refusal to leave it, sometimes makes it possible to obtain “in situ resettlement”, i.e. the official allocation by the state of plots of land to be built on the shantytown site, at subsidised cost. This option, which is optimal in the eyes of the slum dwellers but costly in the eyes of the authorities, allows residents to make a considerable leap up the social ladder without losing their urban bearings or moving away from the informal labour market, which for many is their main source of income. However, few women achieve the desired result. And for those who do, owning a home does not necessarily change the immobility that characterises their daily lives. Home ownership offers little or no economic opportunity and does not weaken the systemic gender and class domination that conditions their inertia. Using a spatial entry point to study the forms of resistance of a minority group certainly highlights the strength of spatial appropriation and the importance of everyday life in the struggle for better living conditions, as well as the great imbalance of power between dominant and dominated that makes “success” stories an exception. In this article, based on empirical work carried out between 2017 and 2019 in the city of Salé (Morocco), I return to the multiple dimensions of immobility that mark the daily lives of the women who inhabit the shantytown, by transcribing these narratives in the form of cartographies of referential and everyday places. Through the use of data collected during semi-structured interviews and on-site observations and surveys, I highlight the appropriation strategies mobilised to overcome this condition of inertia and to exert pressure for a suitable housing solution. The study of women’s sub-political forms of resistance in three shantytowns in the Sidi Moussa district (Salé), and the varied outlets that result from similar strategies, pushes us not only to explore the emancipatory potential of these struggles but also to further unravel the imbalance of power between the established system and the dominated groups.